Conrad, M., Hálfdanarson, G., Michailidou, A., Galpin, C., and Pyrhönen, N. (Εds.) (2023). Europe in the Age of Post-Truth Politics: Populism, Disinformation and the Public Sphere. Palgrave Macmillan. - Gotsis, George (The Greek Review of Social Research, 2023)
N/A